The study of agricultural zakat payment to formal zakat institution among paddy farmers in Kedah - Muhammad Asyraf, Abdul Wahab (2019)
This research aimed to study the agricultural zakat collection to formal zakat institution among paddy farmers in Kedah. Based on three main objectives, this research focus of several main things which is the understanding of farmers, factors of decreasing zakat collection and the improvement for the formal zakat institution. For the first objective, this research explores the knowledge of agricultural Zakat among paddy farmers in Kedah. Secondly, this research also explains the decreasing trend of agricultural zakat collection to formal zakat institutions happens in Kedah. Thirdly, this study also describes the effective action to increase Agricultural zakat collection to formal zakat institution in Kedah. Hence, to make sure all objectives that have been listed are answered progressively, the most suitable method that can used is qualitative research methodology. This research integrated the source of relevant literatures and interviews. At the end of this paper, the researcher found that the level of understanding about agricultural zakat among the farmers is at a moderate level. Besides, the researcher also found several factors that lead to the trend of decreasing of agricultural zakat payment to the formal zakat institution. In addition, the researcher also suggests several improvements to the formal zakat institution in order to overcome the problem that happens. In conclusions, the formal zakat institutions must take several actions to ensure the zakat collection for agricultural can be increased.